Monitoring and Analysis of Honeypot System Performance using Simple Network Management Protocol (SNMP) - Hariri, Imron Kadafi; Subardono, Alif (Journal of Internet and Software Engineering, 2021)
Abstract – Installation of the honepot sensor on Raspberry Pi device integrated with Modern Honey Network(MHN) is a DSSDI UGM action to see the threats of existing public Network, so it can be preventive action. But theinstalled Honeypot sensors sometimes have problems in the form of overload on the System so that data attacks arenot recorded. It is necessary to develop a monitoring System on the Honeypot System to monitor and manage Systemresources and to analyze Honeypot data needs. System monitoring which is one of the Network Management System(NMS) functions can be implemented with Simple Network Management Protocol (SNMP) to monitor theperformance of Honeypot sensor devices. From monitoring the Honeypot System shows the Honeypot sensor deviceoverloaded in memory. In addition, from the monitoring is seen the influence of the number of attacks on Systemperformance. Keywords - Honeypot, Modern Honey Network (MHN), Network Management System (NMS), Simple NetworkManagement Protocol (SNMP)